Eficiência de inseticidas químicos e identificação de mecanismos moleculares de resistência a piretroides em Chrysodeixis includens (Lepidoptera: Noctuidae) - Perini, Clérison Régis (2018)
Larvae of the soybean looper, Chrysodeixis includens (Walker, [1858]) (Lepidoptera: Noctuidae), is the most important soybean caterpillar pest in Brazil due to high tolerance to insecticides and control failures in soybean fields. In this sense, we conducted some researches to evaluate the performance of insecticides against C. includens on soybean in field conditions over three years (2014, 2015, and 2016) and a high-throughput RNA sequencing on two Brazilian populations of C. includens, LAB and MS, differing in susceptibility to pyrethroid λ-cyhalothrin. In the first research, the number of surviving small and large larvae of C. includens was evaluated at 3, 7, and 10 days after spray. Moreover, in 2016 we compared the efficacy of one and two applications of each insecticide within a seven-day interval. In the second research, RNA was extracted from head and thorax + abdomen parts of 3° instar larvae of C. includens susceptible and resistant and paired-end Illumina libraries were generated using the TruSeq® RNA Library Prep Kit. The Illumina data was used to compare the transcriptomes evaluating mutations and a global differential gene expression between these populations. Considering the results of the field trials the majority of insecticides showed low efficacy against larvae of C. includens, over three years of experiments. The insecticides indoxacarb and chlorfenapyr had consistently the highest reduction of larvae of C. includens. The second application of methoxyfenozide, spinetoram, indoxacarb, and flubendiamide+thiodicarb increased efficacy significantly against large larvae. The mixture of chlorfluazuron+acephate reduced defoliation in 2016 but did not effect larval density. Considering the three-year period, these findings demonstrate that few insecticides are effective to cause mortality of C. includens on soybean, suggesting further investigation of insecticide resistance. Some of the insecticides needed a second application to improve efficacy or to reduce the injury on soybean leaves. Based on these results, the grower also has to take into account the cost of these insecticides, because the most effective insecticides in this case are costlier. In the other hand, based on the second research, our results revealed several potential molecular mechanisms on C. includens responsible for its low susceptibility to pyrethroid insecticides. The comparison between sodium channel transcript, which is the target of pyrethroids, resistant vs. susceptible populations, MS vs. LAB, we found five nonsynonymous mutations within the coding region of the voltage gated sodium channel in the resistant population (N1013I, L1314V, Q1433H, F1608C, and P1800S), specifically in domains II, III, and IV. These mutations might alter the protein conformation and reduce sensitivity of connection between pyrethroids and sodium channel. Also, the high abundance of transcripts related to metabolic enzymes including cytochrome p450s, glutathione s-transferases, esterases, and UDP glycosyltransferases, suggests an intense detoxification process of pyrethroid in C. includens. Some of these enzymes were upregulated in the head of the resistant population, suggesting that a detoxification process begins in the mouth parts and continues through the gut. This overexpression of detoxification genes in MS population might be enhanced via a signaling pathway of two overexpressed GPCR genes in the head. In order to compensate the spent energy in the detoxification 15 process, larvae of soybean looper showed high expression of some potential digestive and metabolic energy enzymes such as: trypsin, serine protease, lipase, and chymotrypsin. In addition, cuticle genes were found to be upregulated in the thorax + abdomen, which represents a potential barrier to insecticide penetrate in the resistant larvae. In summary, our findings represent the first insights into the molecular mechanisms underlying insecticide resistance in C. includens. Thus, the management of C. includens in soybean is challenging and the tactics have to be combined in an integrated pest management and insecticide resistance management.